THE FINTECH BOOK: THE FINANCIAL TECHNOLOGY HANDBOOK FOR INVESTORS, ENTREPRENEURS AND VISIONARIES - Fitri Amalia (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
This book review deals with the fiancial technology area in emerging markets. The followings are the data about the book:Keyword:Publisher:Length:Price:Reading rating:Overall rating:financial technology, emerging marketsJohn Wiley & Sons Ltd, West Sussex, United Kingdom (2016)291 pages27.16 (paperback)8 (1 = very difficult; 10 = very easy)3 (1 = average; 4 = outstanding)